2019
DOI: 10.14740/cr924
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Clinical Follow-Up After Thrombolytic Therapy in Patients With Prosthetic Valve Thrombosis: A Single-Center Experience

Abstract: BackgroundThrombolytic therapy has evolved as an alternative to surgery for prosthetic valve thrombosis (PVT). Therefore, this retrospective, single-center study aimed to evaluate the clinical profile of PVT and the role of thrombolytic therapy in patients with PVT.MethodsData from a total of 16 consecutive patients with PVT enrolled between January 2017 and January 2018 at a tertiary care center in India were retrospectively evaluated. PVT was diagnosed based on clinical presentation, transthoracic echocardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
1
0
0
Order By: Relevance
“…Although several overseas studies indicated a greater mean age, exceeding 50 years, the findings of women being more prone to PV thrombosis were similar to ours [17,18]. Numerous research reported that men had a little greater frequency than women, and the mean age was under 40 years [19,20]. As with previous studies that used streptokinase as the thrombolytic agent, 83.3% of patients were successful in thrombolysis [21,22] but Feng et al found that complete success was slightly lower at 69.6% when urokinase was used as the thrombolytic agent.…”
Section: Resultssupporting
confidence: 84%
“…Although several overseas studies indicated a greater mean age, exceeding 50 years, the findings of women being more prone to PV thrombosis were similar to ours [17,18]. Numerous research reported that men had a little greater frequency than women, and the mean age was under 40 years [19,20]. As with previous studies that used streptokinase as the thrombolytic agent, 83.3% of patients were successful in thrombolysis [21,22] but Feng et al found that complete success was slightly lower at 69.6% when urokinase was used as the thrombolytic agent.…”
Section: Resultssupporting
confidence: 84%
“…One of those five patients died in the 4th hour of thrombolytic treatment because of cerebral thrombotic embolization. Risk of the cerebral embolization during thrombolytic treatment of left-sided prosthetic valve thrombosis was reported by several authors [15][16][17][18][19][20].…”
mentioning
confidence: 99%